2013
DOI: 10.5624/isd.2013.43.4.283
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and characteristics of pneumatized articular tubercle: First large series in Iranian people

Abstract: PurposeThis study was performed to determine the prevalence and characteristics of pneumatized articular tubercle or eminence among a defined group of Iranian people.Materials and MethodsDigital panoramic radiographs of 1694 patients in the Department of Oral and Maxillofacial Radiology, Hamadan Dental School, Iran were evaluated retrospectively to detect the above lesion. Finally, 1563 radiographs were selected according to inclusion criteria. Then, a review was done of 10 large case series found using a MEDL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
34
2
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(42 citation statements)
references
References 13 publications
5
34
2
1
Order By: Relevance
“…44 of the PATs were unilocular type, and 66 of the PATs were multilocular typein the study done by Yavuz et al (18). Shokri et al (20) found 53.1% of unilocular and 46.9% of multilocular PAT in their study. 38.5% PAT of unilocular and 61.5% PAT of multilocular type were observed in Orhan and his colleagues' study (8).…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…44 of the PATs were unilocular type, and 66 of the PATs were multilocular typein the study done by Yavuz et al (18). Shokri et al (20) found 53.1% of unilocular and 46.9% of multilocular PAT in their study. 38.5% PAT of unilocular and 61.5% PAT of multilocular type were observed in Orhan and his colleagues' study (8).…”
Section: Discussionmentioning
confidence: 80%
“…Shokri et al (20) evaluated digital panoramic radiographs of 1563 patient with a mean age of 32.6±7.63 years. PAT was found in 98 cases in their study, representing a prevalence of 6.2% with a mean age of 22.8±7.9 and a range of 8 to 60 years .…”
Section: Discussionmentioning
confidence: 99%
“…Surgical procedures involving mandibular condyle and articular eminence can result in inadvertent penetration through the defect, and lead to dural tear and cerebro-spinal fluid leakage [7]. Moreover when ZACD is evident on the preoperative radiograph, eminoplasty or eminectomy are contraindicated [8].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, in the mastoid process, accessory air cells may be able to be located in the adjacent bone. (1)(2)(3) .When these exist in the zygomatic process of the temporal bone, they are known as the pneumatized articular tubercle (PAT) and the pneumatized roof of the glenoid fossa (PRGF). (4,5) This asymptomatic radiolucency in the zygomatic process is similar to mastoid air cells.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the medial portion of the articular eminence could only be thoroughly assessed on CT or CBCT. (2,4,(8)(9)(10)(11)(12) The recognition of these air cells is necessary from a surgical point of view. Penetration through this anatomic finding during surgical procedures may have disastrous outcomes.…”
Section: Introductionmentioning
confidence: 99%